A temperature effect analysis of the KRITZ-1 benchmark based on keff decomposition and using the JENDL-4.0 and ENDF/B-VII.1 libraries. (November 2018) - El Ouahdani, S.; Boukhal, H.; Erradi, L.; Chakir, E.; Azahra, M.; El Bardouni, T.; Makhloul, M.; Ahmed, A.
Abstract: This paper provides a comparison between multiplication factors within the UO2 fuelled cores that were measured during the original KRITZ-1 experiments performed in the early 1970s. Results were calculated using the MCNP6.1 code and the most recent cross section libraries, ENDF/B-VII.1 and JENDL-4.0. The results of this study reveal a good level of agreement between calculated and measured outcomes; indeed, the maximum relative error of calculated keff from experimental data does not exceed 0.5% (absolute value) for all cores and for both evaluations. The reactivity temperature coefficient, expressed as the temperature dependence of the reactivity, was examined into details using the seven factors that incorporate the keff parameter rather than just the five that exist in the literature. In order to better investigate the influence of differences in neutron cross sections we also quantified the temperature effect on the five factors of the infinite multiplication factor on each one separately by admitting a pin cell model. Calculated thermal and fast non-leakage probabilities using JENDL-4.0 are found to overestimate the ones calculated using ENDF/B-VII.1 for all temperatures, possibly because the JENDL-4.0 library overestimates some absorptions, especially in the resonance region of fissionable nuclides. This discrepancy between the libraries decreases with increasing temperature, however, while the inverse tends to occur in the case of standard deviations. Our assessment has shown that the temperature coefficient in the thermal temperature range is linked to thermal spectrum and water density effects, while within the epithermal temperature range this is strongly dependent on the thermal shapes of the cross sections of the uranium isotopes; the resonance escape probability highlights that the error is mainly due to the Doppler broadening effect. Highlights: Seeing that the works on KRITZ-1 are limited over all the world, an analysis of the KRITZ-1 experiments light water moderated lattices with uranium rods, at 20 °C, 90 °C, 160 °C, and 210 °C temperatures; using MCNP6.1 code and the ENDF/B-VII.1 and JENDL-4.0 libraries are made. The reactivity decomposition to seven factors allowed us to make a detailed analyze to the reactivity temperature coefficient and to investigate better the influence of cross sections differences. A detailed analysis has made to the thermal components contribution. The main contributions that led to the RTC are linked to the water density effect. The contribution is very weak and appears as constant with the temperature because it corresponds to the Thermal Spectral Shift effect. An analysis has made for the calculated thermal and fast non-leakage probability. The overall RTC value becomes slightly negative and this effect appears stronger in the temperature range from 160 °C to 210 °C.